Influence of phytogenic feed additives and prebiotic in vegetable protein based diet on broiler performance (Progressive Agriculture, 2018)
This study was conducted to determine the effect of phytogenic feed additive and prebiotic on vegetable protein base diet in broiler performance.  A total of 90 chicks (Cobb-500) were weighted and randomly assigned to the three treatment groups (To, T1 and T2) and supplemented with either phytogenic feed additives or prebiotic and reared for 28 days. Data on live body weight, body weight gain, feed intake and feed conversion (FC) were taken at weekly interval. Results revealed that significant (P0.05) differences were found in live weight gain among the treatment groups on weekly intervals along the whole experimental period. However, significant differences (P